Relations between breast cancer risk and endogenous sex hormones (oestrogen, androgens, progesterone) - Key, T (2003)
Breast cancer risk is increased by an early menarche and by late menopause, suggesting that a prolonged exposure of the breast to high levels of ovarian steroids in pre-menopausal women increases breast cancer risk. Recent prospective studies have shown that post-menopausal women, who develop a breast cancer had during the pre-diagnostic time, oestradiol and other sex hormones blood concentrations significantly higher than the women who remain cancer free. The long-term determination of the hormonal concentrations in pre-menopausal women is difficult, and few prospective studies have been carried out, but the available data agree with the hypothesis that relatively high oestradiol concentrations among pre-menopausal women are associated to an increase in breast cancer risk. In populations with weak prevalence of breast cancer, the women have low blood oestradiol concentrations, both before and after the menopause. Blood oestradiol concentration is probably a major determinant of breast cancer risk, but more data are needed to evaluate the possible roles of other sex hormones.